Enhanced Terahertz Amplification Based on Photo-Excited Graphene-Dielectric Hybrid Metasurface - Shengnan Guan; Jierong Cheng; Tiehong Chen; Shengjiang Chang (Nanomaterials, 2020)
Graphene under optical pump has been shown to be an attractive gain medium with negative dynamic conductivity at terahertz frequencies. However, the amplification over a monolayer graphene is very weak due to its one-atom thickness. In this paper, the proposed graphene-dielectric reflective metasurface effectively improved terahertz field localization and enhanced coherent amplification. The amplification coefficient of 35 was obtained at 3.38 THz at room temperature with an infrared pump intensity of 8 W/mm2. As pump intensity increased from 0 to 15 W/mm2, we observed a loss–gain–loss transition process, which was discussed in detail through coupled-mode theory. In addition, amplification at different frequencies was achieved by merely re-optimizing the geometric parameters of the dielectric resonators. This study offers an effective solution for enhancing terahertz radiation and developing terahertz lasers.